Cesarean sections in Brazil: will they ever stop increasing? - Fernando C. Barros; Alicia Matijasevich; Ana Goretti K. Maranhão; Juan J. Escalante; Dacio L. Rabello Neto; Roberto M. Fernandes; Maria Esther A. Vilella; Ana Cristina Matos; Cristina Albuquerque; Roldofo Gómez Ponce de Léon; Cesar G. Victora
OBJECTIVE: To describe trends, geographic distribution, and risk factors for cesarean deliveries in Brazil in 2000-2011, and to determine if efforts to curtail rates have had a measurable impact. METHODS: This was an observational study using nationwide information from the Department of Informatics of the Unified Health System (DATASUS). Individual level analyses were based on data regarding maternal education, age, parity, and skin color. Ecological analyses at the level of 431 health districts investigated the relationships with health facility density and poverty level. RESULTS: Cesarean rates increased markedly, from 37.9% in 2000 to 53.9% in 2011. Preliminary results from 2012 showed a rate of 55.8%, with the richest geographic areas showing the highest rates. Rates at the municipal level varied from 9%-96%. Cesareans were more common in women with higher education, white skin color, older age, and in primi- paras. In the ecological analyses, the number of health facilities per 1 000 population was strongly and positively correlated with cesarean rates, with an increase of 16.1 percentage points (95% Confidence Interval [95%CI] = 4.3-17.8) for each facility. An increase of 1 percentage point in the poverty rate was associated with a decline of 0.5 percentage point in cesarean rates (95%CI = 0.5-0.6). CONCLUSIONS: The strong associations with maternal education and health facility density suggest that the vast majority of cesareans are not medically indicated. A number of policies and programs have been launched to counteract this trend, but have had virtually no impact.